2014
DOI: 10.6116/kjh.2014.29.6.85.
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different parts of Angelica gigas Nakai on brain damages and neuronal death in transient middle artery occlusion/reperfusion-induced ischemic rats

Abstract: Objectives : We compared with the effects of different parts (root head, root body and hairy root) of Angelica gigas Nakai (Angelicae Gigantis Radix, AG) with on middle cerebral artery occlusion(MCAO)-induced ischemic rats, and on LPS-induced inflammatory response in BV2 microglia. Methods : The 30% ethanol and water extracts of different parts of AG were prepared. Each extract (50 and 100 ㎎/㎏) was administrated intraperitoneally once in MCAO-induced ischemic rats. We measured infarction volumes by TTC stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…There have been previous reports regarding RAG and its constituents' neuroprotective effects [13,14,25], and Shin et al reported that the aqueous extract of RAG attenuated cerebral damage and neuronal death in tMCAO-induced ischemic rats [13]. However, to our knowledge, pharmacokinetics studies on effective dosage of RAG have not been conducted until now.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…There have been previous reports regarding RAG and its constituents' neuroprotective effects [13,14,25], and Shin et al reported that the aqueous extract of RAG attenuated cerebral damage and neuronal death in tMCAO-induced ischemic rats [13]. However, to our knowledge, pharmacokinetics studies on effective dosage of RAG have not been conducted until now.…”
Section: Discussionmentioning
confidence: 98%
“…According to the theoretical basis of Korean medicine, pathological wind contains internal factors caused by liver dysfunction, re is a stressful condition that can cause stroke, sputum can cause hyperlipemia or cerebral thrombosis, and a lack of life can cause a lack of blood circulation in the body [13,32]. RAG has been widely used in various cardiovascular diseases as it has been reported to affect cardiovascular retarded vasodilation, neuroglutamic acid toxicity, and memory impairment [13]. Therefore, these various neuroprotective properties indicate that RAG could be used to treat ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations